IMPROVING STUDENTS’ SPEAKING SKILL THROUGH GROUP INVESTIGATION TECHNIQUE AT XI IPA 2 STUDENTS’ OF SMA NEGERI 1 KOTA SORONG - Marissa S Tupamahu; Vantri Pieter Kelelufna (PEDAGOGIKA: Jurnal Pedagogik dan Dinamika Pendidikan, 2022)
This research used the group investigation technique to improve students’ speaking skills. The subject of this research was the XI IPA 2 of SMA Negeri 1 Kota Sorong, which consisted of 35 students. This study employed "classroom action research," and the data were qualitative. The qualitative data were taken from an observation sheet, a speaking proficiency rubric, a questionnaire, and an interview. The results of the questionnaire show that, overall, students think that the use of the group investigation technique can help students be more active in learning, which has an impact on improving students' speaking skills. Another piece of data that supports student success is the calculation of rubric score data. Based on the results of the rubric score in cycle 1, 3 out of 35 students who managed to meet the good criteria with the results of the classical learning completeness calculation scored only 8 out of 70. In cycle 2, 7 out of 35 students who managed to meet the good criteria with the results of the classical learning completeness calculation scored 20 out of 70. In cycle 3, 25 out of 35 students who managed to meet the good criteria with the results of the classical learning completeness calculation scored 71 out of 70. The number of students who have met the good criteria has increased, as has the completeness of classical learning among students. In other words, students' speaking ability increases and gets better from the first cycle to the third cycle. This proves that the use of the group investigation technique can improve students' speaking skills.